Medidas de absorvância acústica por meio da timpanometria de banda larga em neonatos - Vilela, Cibelle Duarte (2017)
Introduction: Acoustic absorbance measures by wideband tympanometry are performed using the chirp stimulus using a stimulus with frequency spectrum of 226 Hz to 8000 Hz. Objective: To study the results of acoustic absorbance measures using wideband tympanometry in neonates. Method: the sample consisted of 269 subjects who underwent NHS (group I) and eleven who had failed NHS (group II), all of whom were evaluated before hospital discharge. The subjects were characterized in normal auditory status, slight change in the test and changed test, according to the results of screening tests. For the absorbance analysis, eleven frequency bands ranging from 226 to 8000 Hz were selected. Percentile analysis was performed among subjects who presented normal auditory status. Results: Absorbance curves varied between the frequencies of 226 Hz and 8000 Hz, from 0.3 to 0.7 for subjects with normal hearing status in the right ear, from 0,4 to 0,6 for subjects with normal hearing status in the left ear. The subjects in group II had values of absorbance between 0.3 and 0.5 in the right ear and between 0.3 and 0.4 in the left ear. The frequencies from 749.15 to 2000 Hz show significant differences in absorbances. Conclusion: Absorbance values were higher in subjects with normal hearing status and in subjects with changed auditory status before maternity discharge, but normal tests results who were evaluated after 15 days. The percentile curve may contribute to the clinical analysis of the data specially neonates absorvance between 749.15 and 2000 Hz